Security Issues in Cloud Computing - Sharma, Indu; kaur, Mandeep (International Journal of Computer Sciences and Engineering, 2015)
Cloud computing trend is increasing rapidly so to make cloud computing more popular the very first step for the organization is to identify exact area where the cloud related threats lie. At an unusual pace, cloud computing has transformed business and government. And this created new security challenges. The development of the cloud service model provide business – supporting technology in a more efficient way than ever before .the shift from server to service based technology brought a drastic change in computing technology. However these developments have created new security vulnerabilities, including security issues whose full impressions are still rising. This paper presents an overview and study of cloud computing, with several security threats, security issues, currently used cloud technologies and security solutions.